ANALISIS GAYA BAHASA (MAJAS) DAN MAKNA PADA CERPEN “TOMBAK SANG PENENUN“ KARYA BENNY ARNAS (KAJIAN STILISTIKA) - Umu Fadhilah (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
This research problem was about language style and figure of speech in a short story and analyze about short story meaning of " Tombak sang Penenun by Benny Arnas based on stylists study .  Purpose of this research was  knowing use language figure of speech and types figure of speech that was in the novel.  This research use stylists approach  .This  Research data used descriptive data in the form phrases, words, and sentence based on short story of " Tombak sang Penenun by Benny Arnas . The results of the study found that research prove existence there is three  type group figure of speech contained in short story that is  group figure of speech comparison that includes personification , metaphor , and antonomasiai while group figure of speech affirmation there isn’t in this short story.